When the Novice Reader Faces Academic Texts: The Difficult Path From General to Specialized Comprehension - Lobato-Osorio, Lucila (2019)
The academic text is a conventionally structured and scientifically oriented community product that makes use of a specific set of concepts and vocabulary. This paper aims to establish that, due to such characteristics, academic texts present difficulties for the inexperienced reader as they require specialized reading comprehension. To achieve its goal, this paper presents the results of a diagnostic instrument of freshperson’s reading competence level. The test was conducted on 733 new students from the Universidad Icesi in Cali, Colombia, during the first semester of 2017. Based on the discourse analysis and text-linguistics approach, the test was about an explanatory-argumentative text. On a second stage, the paper reviews the characteristics of the academic texts that difficult the reading comprehension by those who are newly integrated into the university. Finally, a series of learning objectives to be included in different courses is proposed in order to support the students’ achievement of specialized reading comprehension.